Information System for Financial Management Advancing Village Community Empowerment Across Bali Province - Nugraha, Putu Gede Surya Cipta; Indrawan, I Putu Yoga; Desmayani, Ni Made Mila Rosa; Mahendra, Gede Surya; Yuliandari, Ni Kadek (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Manual financial recording at the Community and Village Empowerment Service of Bali Province undermines traceability, delays reporting, and heightens the risk of data loss. This study designs and implements a web-based financial management information system that centralizes data capture, processing, storage, and reporting with role-based controls (treasurer, secretary, head of finance). Development followed the waterfall model—requirements definition; system and software design; implementation with unit testing; integration and system testing; and operation and maintenance—supported by clear specifications for security, reliability, and usability. The implemented system manages employee records, cash flows, changes in capital, balance sheets, and income statements, and generates printable managerial reports. Functional verification via black-box testing showed successful execution across all tested pages, indicating correctness of critical workflows (authentication, data entry, and reporting). A user acceptance test involving six finance staff yielded an average score of 81.04%, with the system aspect (appearance and operability) at 82.00%, the user aspect (comprehension and task support) at 77.78%, and the interaction aspect (accessibility and link/page reliability) at 83.33%. These quantitative results indicate that the application meets user needs and is suitable for operational deployment. Practically, adoption is expected to improve transparency, strengthen internal control, accelerate period closing, and reduce operational risk in public-sector finance. The structured lifecycle and role-aware design further provide a foundation for future enhancements, including broader usability evaluations, security hardening under higher loads, integration with e-government data sources, and mobile or offline modules to support bandwidth-constrained environments.